E-082 Venous Vascular Malformation of the Floor of Mouth Masquerading as Dermoid Tumor. (29th July 2016) - Dmytriw, A; Song, J; Gullane, P; terBrugge, K; Yu, E
Abstract : Introduction: Venous vascular malformations (VVMs) are described as abnormal post-capillary lesions which exhibit low flow. These are typically malleable and may grow with endocrine fluctuations. These irregular conduits are often characterized by a soft, compressible, nonpulsatile tissue mass that may exhibit a blue tinge due to the collection of ectatic venous channels underneath the dermis. Further findings upon physical examination may include expansion of the malformation with the Valsalva maneuver, and flattening of the protrusion with applied pressure. A VVM that mimics the classic appearance of dermoid tumor on imaging has never been reported. Case presentation: We encountered a 43 year-old woman with intermittent dysphagia relating to a firm submandibular mass. Physical exam and cross-sectional imaging revealed features consistent with variant dermoid cyst. Gadolinium-enhanced MRI of the mass in T1 and T2 weighted imaging (Figure 1 ) revealed a lesion with T1 hypersensitivity and variable T2 signal. These results were followed-up with CT angiography which showed internal enhancement (Figure 1 ) possibly attributable to saponification, calcification, or rupture of the presumed dermoid cyst. However this pattern of enhancement was felt to be unusual, and digital subtraction angiography was performed to exclude a primarily vascular lesion. Catheter angiography eventually demonstrated a VVM which possessed vessels of variable size and partial thrombosis. Discussion: This case presented a significant diagnostic challenge to our team as the VVM possessed numerous idiosyncratic features prevalent in cases of dermoid cysts, with simultaneous findings that are contraindicative of most venous malformations. The regression of the VVM during the patient's pregnancy was counterintuitive to expectation, as endocrine fluctuations would be expected to precipitate rapid enlargement of the lesion. Similarly, the abnormal firmness of the mass discouraged the diagnosis of a VVM which is characteristically soft on palpation, but this may be explained by the presence of partially thrombosed vessels. We report the case and propose that catheter angiography remains important in cases where vascular malformation is considered. Disclosures: A. Dmytriw: None. J. Song: None. P. Gullane: None. K. terBrugge: None. E. Yu: None.